2019
DOI: 10.1111/geoj.12314
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural innovation and environmental change on the floodplains of the Congo River

Abstract: Climate‐driven environmental changes bring new risks but also opportunities to populations living along the world's major rivers. Based on ethnoecological fieldwork, in this paper we examine how people living in the cuvette centrale of the Congo basin have adopted flood‐recession agriculture on islands in the Congo River, taking advantage of a secular shift since the 1980s in the hydrological regime of the Congo River. Analyses of the hydrological data reveal that this shift decreased flood risk and significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 30 publications
0
5
0
1
Order By: Relevance
“…Riverine islands provide unique habitat diversity (Gurnell & Petts, 2002;Ward et al, 2000) and, as suggested by the present investigation, unique agro-ecosystems when found in adaptive socio-ecological systems characterized by moderate human pressures on the environment like in the Upper Huallaga. Besides our case study, other evidence has been provided of the productive use of fluvial islands in tropical areas by communities living along the rivers (Comptour et al, 2020;Kotoky et al, 2003;Prashnani et al, 2019;Sarker et al, 2020). This anthropogenic impact can be viewed as moderate, allowing these rivers to still keep their free-flowing character, according to Grill et al (2019).…”
Section: Broadening the Viewpoint Of Riverine Islands As Parts Of Cassmentioning
confidence: 58%
See 2 more Smart Citations
“…Riverine islands provide unique habitat diversity (Gurnell & Petts, 2002;Ward et al, 2000) and, as suggested by the present investigation, unique agro-ecosystems when found in adaptive socio-ecological systems characterized by moderate human pressures on the environment like in the Upper Huallaga. Besides our case study, other evidence has been provided of the productive use of fluvial islands in tropical areas by communities living along the rivers (Comptour et al, 2020;Kotoky et al, 2003;Prashnani et al, 2019;Sarker et al, 2020). This anthropogenic impact can be viewed as moderate, allowing these rivers to still keep their free-flowing character, according to Grill et al (2019).…”
Section: Broadening the Viewpoint Of Riverine Islands As Parts Of Cassmentioning
confidence: 58%
“…For centuries, agricultural practices in floodplains have been adapted to river regimes: in the Amazon region, people take advantage of the proximity to the water source and of seasonal flow pulses (Coomes et al., 2016; Denevan, 1982; Hiraoka, 1985; IIAP, 2018). These strategies also include specific adaptations in relation to fluvial islands, were agricultural, and occasionally other human activities, (Comptour et al., 2020), coexist with flow disturbance and river morphodynamics. Notwithstanding a large number of studies on riverine islands, little literature delved into their agricultural exploitation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Si certains champs surélevés sont abandonnés, d'autres sont toujours cultivés. Ils exigent plus de main-d'oeuvre que la culture sur terre ferme, la culture sur brûlis ou l'agriculture de décrue, mais leur rendement est plus élevé et le risque d'inondation est moindre (Comptour et al 2020). Actuellement, les communautés des tourbières pratiquent la chasse, la pêche, le ramassage de produits forestiers tels que les frondes des palmiers pour construire des toitures.…”
Section: L'agricultureunclassified
“…Under this farming system, farmers grow crops outside the rainy season, thus giving them an opportunity to secure food throughout the year and earn additional income. The removal of water and nutrient‐related constraints affords smallholder farmers the opportunity to venture into high‐value crops and earn high incomes (Balana et al, 2019; Comptour et al, 2020; Sidibé et al, 2016). Crops grown under FRC in SSA are diversified and they include food and cash crops (Table 1).…”
Section: Introductionmentioning
confidence: 99%